2015
DOI: 10.1159/000374074
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde Prevents Endothelial Dysfunction Induced by High Glucose by Activating Nrf2

Abstract: Background/Aims: It is well documented that hyperglycemia-induced oxidative stress is an important causative factor of endothelial dysfunction. Cinnamaldehyde (CA) is a key flavor compound in cinnamon essential oil that can enhance the antioxidant defense against reactive oxygen species (ROS) by activating NF-E2-related factor 2 (Nrf2), which has been shown to have a cardiovascular protective effect, but its role in endothelial dysfunction induced by high glucose is unknown. Methods: Dissected male C57BL/6J mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 29 publications
3
73
1
1
Order By: Relevance
“…Previous studies have demonstrated that the expression of Nrf2 and HO-1 at protein and mRNA levels markedly increased in hippocampus of amygdala kindling rats [55, 56]. Moreover, activation of Nrf2-ARE signal pathway in hippocampus reduced the progression of amygdale kindling, and alleviated the cognitive impairment and oxidative stress induced by epileptic seizure [21, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the expression of Nrf2 and HO-1 at protein and mRNA levels markedly increased in hippocampus of amygdala kindling rats [55, 56]. Moreover, activation of Nrf2-ARE signal pathway in hippocampus reduced the progression of amygdale kindling, and alleviated the cognitive impairment and oxidative stress induced by epileptic seizure [21, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamon, which is used as an herbal drug and spice, has been employed to treat obesity and diabetes for thousands of years in traditional Chinese medicine [20]. CA, the main volatile oil constituent of cinnamon, exhibits glucose-lowering activity [21]. Furthermore, CA positively alters body composition in vivo [22, 23] and regulates adipocyte differentiation in vitro [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor 2 (Nrf2) is a key regulator of oxidative stress and the inflammatory response in endothelial cells [16, 17]. Nrf2 binds to the antioxidant response element (ARE) and triggers the expression of ARE-regulated genes, including heme oxygenase-1 (HO-1).…”
Section: Introductionmentioning
confidence: 99%